Clinical and tomography evolution of frontal osteomyelitis: Case report - Verde, Raquel Crisóstomo Lima; de Souza, Luana Alves; Lessa, Bruno Farias; de Lima, Clara Mônica Figueiredo; Lessa, Marcus Miranda; Lessa, Hélio Andrade (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The frontal osteomyelitis is a complication of rhinosinusitis which can evolve to acute or chronicle. There is inflammatory reaction by the increasing of intraosseous pressure, ischemia and local necrosis, leading to bone abscess formation. There is no drainage, it will occur detachment of the periosteum, soft tissue invasion and worsening of ischemia with subsequent bone sequestration.Method: Case report of an inpatient in an emergency service of another institution by the complication of rhinosinusitis who was referred to the Otorhinolaryngology Service of University Hospital Professor Edgard Santos of Federal University of Bahia.Case Report: Male patient, 16 years-old, presented himself to the ER of another institution with cephalea, vomits and fever which evolved to periorbital edema and frontal to the left, moving to palpebral fluctuation and frontal. Subjected to frontal and palpebral abscess drainage, with broad-spectrum antibiotic therapy with no improvement. He was referred to our service keeping edema and fluctuation in region frontal and light edema in left periorbital region. The nasal endoscopy showed edema in meatus to the left and the computerized tomography showed fronto-ethmoid sinusitis to the left and signs of frontal osteomyelitis with bone sequestration and epidural empyema. Subjected to sinasal endoscopy surgery, external Access or removal of the frontal one affected and epidural empyema drainage. Evolved to the remission of the disease.Final Considerations: Failure in the diagnosis and rhinosinusitis complication treatment can lead to sequalae and fatal complications. The diagnosis of the frontal osteomyelitis is confirmed by the clinical suspicion and confirmed by radiological examination. The surgery is indicated when the evolution is insidious, there is bone sequestration and intracranial complications.
Keywords: osteomyelitis; frontal sinusitis; tomography; evolution